The Use of Audio-Visual Media in Islamic Cultural History Education: An Ethno Pedagogical Approach in High School - Khatimah, Husnul; Umrati, Umrati; Muhsyanur, Muhsyanur (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This study investigates the implementation of Islamic Cultural History lessons at MAN 1 Poso, focusing on the use and effectiveness of audio-visual media. Conducted using a qualitative method, the research applied an ethnopedagogical approach with data collected through observation, interviews, and documentation. Data were analyzed through reduction, presentation, and conclusion verification. The results indicate that Islamic Cultural History lessons are generally well-implemented, using the "Independent Curriculum" for Phases E and F and the 2013 Curriculum for Grade XII. Audio-visual media, supported by infrastructure such as LCD projectors and Wi-Fi, enhances learning. Its use in Class X E1 effectively increases students' interest and motivation. This study highlights the importance of integrating audio-visual media with appropriate teaching methods to create an engaging learning environment and achieve educational goals. These findings provide valuable insights for future research on the integration of media in Islamic Cultural History education.